Ambitions for palliative and end-of-life care. - Wee, B (Royal College of Physicians, 2016)
The publication of the "Ambitions for palliative and end of life care: a national framework for local action 2015–2020" in September 2015 represents a new milestone in England for all who want to ensure that everyone with advanced, progressive, life-limiting illness has the best possible experience of care throughout their remaining life, and in death. This comes less than 30 years after palliative medicine was formally recognised as a specialty within the Royal College of Physicians and less than 10 after the term ‘end-of-life care’ was formally defined as ‘last year of life’ in the first national End of Life Care Strategy in 2008. In practice, although the definition of ‘end-of-life care’ is time-based and ‘palliative care’ is needs-based, the approach is similar. Like respiratory, cardiac, renal and most other specialties, palliative care has both generalist and specialist components, so all doctors need to be able to deliver this kind of care well, involving palliative medicine specialists when they reach the limits of their competence and confidence.